2011
DOI: 10.1063/1.3605517
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a temperature dependent bandgap on the energy scale of modulated photocurrent experiments

Abstract: Amorphous semiconductors and chalcogenide glasses exhibit a high density of localized states in their bandgap as a consequence of structural defects or due to a lack of long range order. These defect states have a strong influence on the electronic transport properties. Thus, many theories attribute the “resistance drift” or the “threshold switching” effects, both observed in amorphous phase change alloys, to defects within the bandgap. The energetic distribution of states within the bandgap can be probed via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…An ohmic regime of conductivity can be observed for all materials down to the lowest temperatures (see supplementary material 17 ). Furthermore, the measured activation energy for our GeTe and GST devices with tungsten electrodes is $0.37 eV and is in line with values measured on GeTe and GST on aluminum 35 or gold electrodes, 19 i.e., $0.4 eV at room temperature. This value corresponds well to half the optical band gap in all materials studied.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…An ohmic regime of conductivity can be observed for all materials down to the lowest temperatures (see supplementary material 17 ). Furthermore, the measured activation energy for our GeTe and GST devices with tungsten electrodes is $0.37 eV and is in line with values measured on GeTe and GST on aluminum 35 or gold electrodes, 19 i.e., $0.4 eV at room temperature. This value corresponds well to half the optical band gap in all materials studied.…”
Section: Discussionsupporting
confidence: 64%
“…Various studies of the density of states of GeTe have indicated the presence of both a valence-band tail and deep defects. 30,35 Apart from the energetic positions and magnitudes of these defects, the external circumstances under which a specific defect can dominate field assisted emission depend on additional parameters. These parameters are for instance the potential to be chosen in the evaluation of field assisted emission (at low fields) and the effective mass m*, which strongly influences tunneling (at high fields).…”
Section: Behavior At High Fields-full Tunneling Modelmentioning
confidence: 99%
“…This result agrees that ESR signals are not observed in dark conditions even existing defect states in amorphous chalcogenides. Sub-gap states in amorphous Ge 2 Sb 2 Te 5 were investigated using modulated photocurrent measurement (MPC) [11]. MPC spectra show that the position of the deep defect is at midgap.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of this procedure is presented in Ref. 18. data, corrected for the band gap variations, we have obtained for one of the a-GeTe films studied.…”
Section: Resultsmentioning
confidence: 99%